Peran rasio high fructose corn syrup terhadap sukrosa dalam mengatur sifat fisikokimia dan organoleptik snack bar beras merah - Devondra Christabella Glenys Dealyn; Maria Goretti M. Purwanto; Ignasius Radix Astadi Praptono Jati; Erni Setijawati (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
A snack bar as a food product consumed by children and adults on various occasions is usually produced from flour or a mixture of rice puffs that have white rice as the main ingredient. However, this research aimed to determine the effect of High Fructose Corn Syrup (HFCS) to Sucrose ratio on red rice snack bar's physicochemical and organoleptic properties, as well as the best ratio to achieve desired characteristics such as being sturdy, compact, and easy-to-bite. An addition of hydrocolloids like gelatin (12%) is required to preserve the product’s chewiness, by aiding the texture's transformation into a compact and desirable shape, with soft and easy-to-bite characteristics. The result showed different HFCS:Sucrose ratios tend to affect moisture content, water activity, texture, taste preference, hardness, and stickiness of the red rice snack bar. Also, based on the organoleptic test, 12.5:27.5 was the best HFCS:Sucrose ratio used to obtain a final product with an average moisture content of 3.66%, a water activity of 0.403, texture score of 83.81N, and hedonic values 5.08 for taste, 4.75 for hardness, and 4.42 for stickiness.